Retinoic acid signalling inhibits myogenesis by blocking MYOD translation in pig skeletal muscle cells - Changying Wang; Ruige Liu; Wenzhe Luo; Pengxiang Zhao; Heng Wang (Animal Biotechnology)
Vitamin A is an essential nutrient in animals, playing important roles in animal health. In the pig industry, proper supplementation of vitamin A in the feed can improve pork production performance, while deficiency or excessive intake can lead to growth retardation or disease. However, the specific molecular mechanisms through which vitamin A operates on pig skeletal muscle growth as well as muscle stem cell function remain unexplored. Therefore, in this study, we isolated the pig primary skeletal muscle stem cells (pMuSCs) and treated with retinoic acid (RA), the natural metabolite of vitamin A, and then examined the myogenic capacity of pMuSCs via immunostaining, real-time PCR, CCK8 and western-blot analysis. Unexpectedly, the RA caused a significant decrease in the proliferation and differentiation of pMuSCs. Mechanistically, the RA addition induced the activation of retinoic acid receptor gamma (RARγ), which inhibited the myogenesis through the blockage of protein translation of the master myogenic regulator myogenic differentiation 1 gene (MYOD). Specifically, RARγ inactivate AKT kinase (AKT) signalling and lead to dephosphorylation of eukaryotic translation initiation factor 4E binding protein 1 (eIF4EBP1), which in turn repress the eukaryotic translation initiation factor 4E (eIF4E) complex and block mRNA translation of MYOD. Inhibition of AKT could rescue the myogenic defects of RA-treated pMuSCs. Our findings revealed that retinoid acid signalling inhibits the skeletal muscle stem cell proliferation and differentiation in pigs. Therefore, the vitamin A supplement in the feedstuff should be cautiously optimized to avoid the potential adverse consequences on muscle development associated with the excessive levels of retinoic acid.